Competition, resources and the ant (Hymenoptera: Formicidae) mosaic: A comparison of upper and lower canopy - Ribeiro, S.; Espirito Santo, N.; Delabie, J.; Majer, Jonathan (Springer, 2013)
A canopy crane was used to assess ant defensive behaviour and recruitment at baits in the Parque Natural Metropolitano, Panama. Sardine-honey baits were set within a grid of 25 paired upper and lower canopy points, for which coordinates and height were recorded. We tested the hypothesis that interactions in the ant mosaic become stronger as one moves from the lower to the upper canopy. We sampled 23 ant species, with Azteca (A. trigona, A. velox, Azteca nr. chartifex, and A. snellingi) being by far the most abundant genus, recruiting to 63% of baits and excluding all other ant genera. Camponotus (Myrmobrachys) sp. 1 also showed a statistically significant exclusion of other ant species over 95% of its occurrence. Cephalotes umbraculatus and Dolichoderus bispinosus had exclusive occurrences in smaller areas. Exclusion between dominant or subdominant species was more frequent in the upper than lower canopy. Permeable borders and territory-free spaces are important for ant species diversity, and were more frequent in the lower canopy. Here, a combination of more costly patrolling conditions and less profitable resources, such as extra-floral nectaries and trophobionts, may be the most likely cause of this pattern. The findings presented here could account for the viewpoint of some that ant mosaics exist in plantations but not necessarily in tropical forest canopies.